Factors influencing stress and coping strategies among critical care nurses: A cross-sectional analysis - Maha Subih; Husam Al Khamaiseh; Lourance Al Hadid; Yaqeen Al-Jaafreh; Rami A. Elshatarat; Zyad T. Saleh; Wesam T. Almagharbeh; Amal A. Alasmari; Ghaida S. Alsulami; Hekmat Yousef Al-Akash (Journal of Education and Health Promotion)
BACKGROUND: Critical care nurses (CCNs) experience serious work-related stress due to a myriad of factors, like insufficiently trained staff, shortages, and high workloads. They might develop healthy or unhealthy coping strategies. The aim of this study was to measure stress levels and determine coping strategies among CCNs. It also aimed to explore the correlation between stress and coping mechanisms and identify differences in the demographic characteristics and work-related factors with the measured levels of stress and coping mechanisms. MATERIALS AND METHODS: This study employed a cross-sectional design during the COVID-19 pandemic, collecting data from 200 CCNs via an online questionnaire. The survey included a demographic sheet, the Perceived Stress Scale (PSS), and the Ways of Coping Questionnaire (WCQ). Data analysis utilized both descriptive and inferential statistics. Pearson correlations, t-tests, and ANOVA were used to analyze stress, coping mechanisms, and demographic factors, providing insights into CCNs’ stress and coping strategies. RESULT: Most participants were single, held a bachelor’s degree, and worked as staff nurses. Moderate to high stress levels were reported, with the most frequently used coping mechanism being a refuge in fate, and the least utilized being a refuge in supernatural forces. Significant positive correlations were found between stress levels and coping strategies such as keeping to self (r = 0.22, P < 0.05), escape-avoidance (r = 0.33), accepting responsibility (r = 0.37), and refuge in fate (r = 0.18). Additionally, stress was negatively correlated with age (r = −0.17, P = 0.02) and positively associated with night shifts (f = 3.22, P = 0.04), high nurse-to-patient ratios (1:5 and above) (f = 2.42, P = 0.048), and working in military hospitals (f = 3.25, P = 0.04). Coping mechanisms were positively correlated with age and experience, with planful problem-solving showing significant positive correlations with both age (r = 0.18, P = 0.03) and years of experience (r = 0.19, P = 0.007), suggesting that older and more experienced nurses are more likely to use this strategy. CONCLUSIONS: It is recommended that extra effort should be given to CCNs’ ability to adapt to stressful situations. It is possible to improve the retention rates of new nurses by improving their ability to accommodate and by assisting them in developing healthy coping strategies.